Student’s Perception on Using Instagram in Learning English - Rosmiana, Sri; Rahmaeni, Rahmaeni; Musdalifah, Musdalifah (Edumaspul: Jurnal Pendidikan, 2024)
This study investigated the Students’ Perceptions on using instagram in learning english”. A qualitative research design was used in this study. The participants are 15 students from English education at Muhammadiyah University of Enrekang. The instruments used to collect the data were questionnaire. The questionnaire consisted of 30 statements. Google Form was used to obtain the data and the result was used to analyze the data. As a result of the study, the researcher concluded that the benefits of online reading in instagram have had a substantial effect on the knowledge of students’, and the students have strongly focused on the educational evaluation they read during learning. The data reported the highest percentage is 47% of the students agreed that instagram media supported their activity in reading during learning. However the lowest percentage is 7% of the students disagreed that instagram media supported their activity in reading during learning. It shows that students' perceptions are considered positive because most of the students agree that learning on instagram helped them to improve their reading comprehensions skills